THE IMPACT OF THE HALAL INDUSTRY AND ISLAMIC FINANCIAL ASSETS ON INDONESIA'S ECONOMIC GROWTH USING THE VECTOR AUTOREGRESSION (VAR) APPROACH - Imsar Imsar; Nurhayati Nurhayati; Isnaini Harahap; Purnama Ramadani Silalahi (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya(STIESIA) Surabaya, 2024)
The present study intends to examine the influence of the halal business and Sharia financial assets on economic growth in Indonesia. The research method requires a quantitative methodology. Research data was acquired in time series form from the Central Statistics Agency (BPS), Financial Services Authority (OJK), and State of the Global Islamic Economy Report (SGIE). The VAR approach is used for analysis once the data is interpolated monthly. The findings in this research suggest a favorable and significant association between the halal industry and economic growth in Indonesia in the short term. Meanwhile, Islamic financial assets significantly affect economic growth in Indonesia. According to the results of the Granger causality test, a one-way causal relationship exists between economic development in Indonesia and the halal industry. The research results demonstrate that the halal industry is essential in supporting economic growth in Indonesia. With this research, the halal industry and Sharia financial assets can improve Indonesia's economic growth by increasing the halal sector.